Implementação de sistema de autoatendimento acadêmico por meio de terminais de acesso como ferramenta de gestão educacional e administrativa na Universidade Federal de Santa Maria - Alencastro, Marcos Vinicius Dutra (2019)
This dissertation was developed in the line of research on Network Educational Technologies, in the Area of Concentration Educational Technologies in Network for Innovation and Democratization of Education, in the Master Course on Educational Technologies in Network of the Federal University of Santa Maria, as a study aimed at the possibility of implementing access terminals at the Federal University of Santa Maria. It covers more specifically the Department of Registry and Academic Control (DERCA), representing an exploratory study, addressing the reasons that lead to the use of access terminals to be an effective solution to the challenges and problems related to physical spaces and to the time that the use of the conventional practices provoke in the activities that occur in academic every day. The present study is characterized as applied, quantitative and explanatory research. A case study is carried out, with data collection from the Department of Registry and Academic Control (DERCA) and students from the Federal University of Santa Maria. The number of requests for documents, the requested documents and the estimated time for the service, and the technologies used by the department to meet the demand, from which the break-even point is calculated, were analyzed. , the effectiveness of the implementation of terminals for access to services provided at the Federal University of Santa Maria. As a product of this research and from its results, it was proposed the implementation of a self-service system through access terminals to meet the demands of the academic community of the Federal University of Santa Maria.